Fabrication of high aspect ratio micro electrode by using EDM - Elsiti, N.M. (Institute of Physics Publishing, 2016)
The electrical discharge machining (EDM) process inherits characteristics that make it a promising micro-machining technique. Micro electrical discharge machining (micro- EDM) is a derived form of EDM, which is commonly used to manufacture micro and miniature parts and components by using the conventional electrical discharge machining fundamentals. Moving block electro discharge grinding (Moving BEDG) is one of the processes that can be used to fabricate micro-electrode. In this study, a conventional die sinker EDM machine was used to fabricate the micro-electrode. Modifications are made to the moving BEDG, which include changing the direction of movements and control gap in one electrode. Consequently current was controlled due to the use of roughing, semi-finishing and finishing parameters. Finally, a high aspect ratio micro-electrode with a diameter of 110.49Î¼m and length of 6000Î¼m was fabricated. Â© Published under licence by IOP Publishing Ltd.